Hubungan Antara Pengetahuan dengan Upaya Pencegahan Kekambuhan Pada Pasien Demam Typhoid di Rumah Sakit Mandaya Karawang : Penelitian - Bona Dwiramajaya Hartoyo; Evi Deviyana; Pandu Dewi Setyaputri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Typhoid fever is one of the endemic diseases in Indonesia. Typhoid fever is transmitted through food and drink contaminated with Salmonella typhi bacteria. The number of incidences of typhoid fever can be influenced by a lack of knowledge and efforts to prevent its recurrence with salmonella typhi bacteria. The number of incidences of typhoid fever can be influenced by a lack of knowledge and efforts to prevent its recurrence. The purpose of this study was to determine the relationship between knowledge and efforts to prevent recurrence in typhoid fever patients at Mandaya Karawang Hospital. This research method is correlational-descriptive with a cross-sectional approach and was conducted in February until March 2023. The total population were 100 respondents using the accidental sampling technique, with a total of 50 respondents. The results of statistical tests using Chi-square obtained a P value of 0.002 (P value = 0.05), so it can be concluded that there is a significant relationship between knowledge and efforts to prevent recurrence in typhoid fever patients at Mandaya Karawang Hospital.